ACCESSIBILITY STANDARD OF PRIMARY SCHOOL WITHIN KANKE LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Bature, Y. A.; Barki, J. J. (FUDMA Journal of Sciences, 2023)
The relevance of site planning in journey to and from school revolves around accessibility. Rural residential location is a function of accessibility and distance. Town and school planners try to ensure pupils travel distance do not affect their academic performance, hence it’s stipulated 32.00>26.30 as school attendance is a function of distance from pupil home. PCC test of distance reliability with 95% test of confidence; 0.05 revealed H2; School attendance is affected by distance. Commendation is school planners should comply with stipulated accessibility standard, the establishment of school clinic.
Keywords: Accessibility, Site planning, Residential location and Travel Hazard